1997
DOI: 10.3109/00016359709059206
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of malocclusion in 6-year-old Icelandic children: A study using plaster models and orthopantomograms

Abstract: The prevalence of different malocclusion features was investigated in 396 6-year-old Icelandic children, using the epidemiologic registration method described by Björk et al. in 1964. Girls were ahead of boys with regard to dental stage (P < 0.01). One or more permanent teeth were congenitally missing in 5% of the children. Postnormal occlusion was found in 27% of the boys and in 31% of the girls, and prenormal occlusion was found in 6% and 5%, respectively. Straight terminal plane at the second deciduous mola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(20 citation statements)
references
References 11 publications
0
18
0
2
Order By: Relevance
“…Studies on the prevalence of occlusal anomalies in the age group of 5–7-year-olds are rare and results vary greatly, from 36% to almost 80% [3,4,23]. We found that 71.4% of children had some kind of abnormal occlusal trait.…”
Section: Discussionmentioning
confidence: 65%
“…Studies on the prevalence of occlusal anomalies in the age group of 5–7-year-olds are rare and results vary greatly, from 36% to almost 80% [3,4,23]. We found that 71.4% of children had some kind of abnormal occlusal trait.…”
Section: Discussionmentioning
confidence: 65%
“…[12] However, the estimated rate falls short of the published data on samples of orthodontic patients. [2930] A possible explanation may be the higher dental awareness and esthetic anxiety of individuals seeking orthodontic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies on the prevalence of lateral incisor agenesis and canine impaction in different populations, demonstrate rates of 0.8-2%[123] and 0.2-2.8%,[45] respectively. Generally, congenital absence of teeth results from disturbances during the initial stages of tooth development, while eruption failure is caused by displacement of a permanent tooth from its normal eruption path, occasionally due to interference by pathological entities such as odontomas.…”
Section: Introductionmentioning
confidence: 99%
“…Congenital missing of teeth (CMT) or dental agenesis is a common dental abnormality, in which some dental buds fail to develop, leaving an empty space in the arch which causes numerous complications [ 1 – 19 ]. In most countries, out of every 10 to 20 individuals, at least one suffers from agenesis of at least one or two permanent teeth [ 1 , 3 13 , 16 109 ]. It is of importance since not only it is very frequent (as the most common dental anomaly) [ 1 14 ], but also it needs difficult and expensive treatments [ 19 , 105 , 110 , 111 ].…”
Section: Reviewmentioning
confidence: 99%